PTU-053 Is procollagen III aminopeptide a good predictor of liver fibrosis in patients with psoriasis on methotrexate therapy?. (23rd September 2015) - Walsh, K; Riley, S; Lim, Y C; Dhar, A
Abstract : Introduction: The prevalence of hepatotoxicity in long-term methotrexate therapy is around 0–4%. The British Association of Dermatology recommends procollagen III aminopeptide (PIIINP) level monitoring to identify patients at risk of hepatotoxicity with a view to liver biopsy while North American guidelines recommend liver biopsy based on cumulative dose of methotrexate. Methods: 1. To correlate the accuracy of abnormal PIIINP level to predict liver fibrosis in patients receiving long-term methotrexate for psoriasis. 2. To assess adherence to the British Association of Dermatology guidance for PIIINP monitoring. The histology database (SNOMED) was interrogated for a 5-year period (1 January 2003 to 31 December 2007) to find all patients whose liver biopsies had been reported to show fibrosis, and patients with psoriasis identified. Case notes were reviewed for all psoriasis patients on long-term methotrexate. Levels of PIIINP, cumulative methotrexate dosage, comorbidities, drug history, alcohol intake, liver histology and clinical decision following liver biopsy (continuation or stoppage of methotrexate) were recorded. Results: 578 liver biopsies during this period yielded 38 patients receiving methotrexate. 7 patients had methotrexate for another condition and were excluded; a further nine were excluded due to lack of case notes or repeat biopsies for follow-up. 22 patients with psoriasis had liver biopsies while on methotrexate treatment, of which 18 had elevated PIIINP levels above recommended threshold for liver biopsy and four patients had clinician decided biopsies. The mean cumulative dose of methotrexate to first biopsy was 3.86 g (range 0.69 g–9.25 g). The mean time to first biopsy was 4.2 years (range 1.1–10.1 years). 2 patients had PIIINP levels above 8 μg/l, one of which had grade 2 fibrosis on biopsy; the remaining 16 had PIIINP between 4.2 and 8 μg/l and two had Grade 2 fibrosis in this group. Liver histology (n=21): 15 patients had steatosis, three patients had grade 2 and one patient had Grade 1 fibrosis and two patients had normal liver histology. Clinical Outcome: four patients with fibrosis had methotrexate stopped as a result of the biopsy findings and the rest were continued (80%). Conclusion: 19/21 (90%) patients with abnormal PIIINP had abnormal liver histology, but only 19% had fibrosis sufficient to discontinue treatment. PIIINP therefore did not correlate well with liver fibrosis. Newer non-invasive methods such as Fibroscan® may assess fibrosis better in this group of patients and need to be studied.